1990
DOI: 10.1295/polymj.22.1105
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of m-Chlorophenylacetylene Initiated by [Rh(norbornadiene)Cl]2-Triethylamine Catalyst Containing Long-Lived Propagation Species

Abstract: KEY WORDSLong-Lived Propagating Species / Rhodium Complex Catalyst / m-Chlorophenylacetylene / In recent years there has been a growing interest in the polymerization of aromatic acetylenes using transition metal catalysts. Several investigations have been described in the literature, 1 -4 including the living polymerization of ortho substituted phenylacetylenes by Mo-based catalyst. In our preliminary experiments, the polymerization of chlorinated phenylacetylenes, for example, o-chlorophenylacetylene ( o-CPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
164
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 207 publications
(166 citation statements)
references
References 9 publications
1
164
1
Order By: Relevance
“…2 It has been proposed that the effect of the solvents is to promote In a previous article we reported that phenylacetthe efficient dissociation of the dimer complex ylene (PA), 1 its homologues, 2 a-naphthylacety-[Rh(NBD)Cl] 2 into the monomeric species, which lene, 3 and alkylpropiolates, 4,5 and pentynoate 6 may be an important initiation species for this can be stereospecifically polymerized in the prespolymerization, 1,7 as shown in Scheme 1. Further, ence of a Rh complex, [Rh(norbornadiene)Cl] 2 , the structural differences observed between poly-[Rh(NBD)Cl] 2 , when triethylamine (TEA) or an pentynoates prepared with the Rh complex cataalcohol is used as the polymerization solvent and lyst and with metathesis catalysts such as WCl 6 that the helical cis-transoid isomer were selecwas interpreted in terms of the difference in geotively formed in high yields under mild conditions.…”
Section: Introductionmentioning
confidence: 99%
“…2 It has been proposed that the effect of the solvents is to promote In a previous article we reported that phenylacetthe efficient dissociation of the dimer complex ylene (PA), 1 its homologues, 2 a-naphthylacety-[Rh(NBD)Cl] 2 into the monomeric species, which lene, 3 and alkylpropiolates, 4,5 and pentynoate 6 may be an important initiation species for this can be stereospecifically polymerized in the prespolymerization, 1,7 as shown in Scheme 1. Further, ence of a Rh complex, [Rh(norbornadiene)Cl] 2 , the structural differences observed between poly-[Rh(NBD)Cl] 2 , when triethylamine (TEA) or an pentynoates prepared with the Rh complex cataalcohol is used as the polymerization solvent and lyst and with metathesis catalysts such as WCl 6 that the helical cis-transoid isomer were selecwas interpreted in terms of the difference in geotively formed in high yields under mild conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 depicts the CD and UV-vis spectra of the polymers with R 1 ¼ CH 3 and R 2 ¼ C 2 H 5 , n-C 4 H 9 , C(CH 3 ) 3 . Although poly(3) exhibited a different CD pattern from those of poly (1) and poly (2), all these polymers showed UV-vis absorption at 310 nm, indicating the absence of a substituent effect on the conjugation length.…”
Section: Polymerizationmentioning
confidence: 88%
“…2 When appropriately chiral groups are substituted, polyaceytlenes form a helical structure with predominantly one-handed screw sense due to the rigid main chain. In the cases of poly(1-alkyne)s, 3 poly(phenylacetylene) derivatives, 4 and poly(propiolic ester)s, 5 bulky substituents stabilize the helical structure.…”
mentioning
confidence: 99%
“…[35][36][37] The polymerizations of monomers 1a-e were carried out in THF with [(nbd)RhCl] 2 /Et 3 N catalyst, whose results are listed in Table 1. Monomers 1a-c containing Schiff-base groups gave polymers 2a-c as methanol-insoluble products with fairly high molecular weights (M n 5 4.7 3 10 4 to 6.0 3 10 4 ) in high yields (91-97%).…”
Section: Monomer Synthesis and Polymerizationmentioning
confidence: 99%